Prevalence Rate and Risk Factors of Victimization in Adult Patients With a Psychotic Disorder: A Systematic Review and Meta-analysis - de Vries, Bertine; van Busschbach, Jooske T; van der Stouwe, Elisabeth C D; Aleman, André; van Dijk, Jan J M; Lysaker, Paul H; Arends, Johan; Nijman, Saskia A; Pijnenborg, Gerdina H M (Schizophrenia bulletin, 2019)
Abstract Psychotic disorders often have been linked with violence. However, studies have shown that people with a psychotic disorder are more often victim than perpetrator of violence. The objective of this meta-analysis was to review prevalence rates for different types of victimization and to identify risk factors associated with victimization. Based on a search in MEDLINE, PsycINFO, and Web of Science, 27 studies were found with samples consisting of adults with a psychotic disorder and possible victimization occurring during adulthood and data on “violent victimization,” “sexual victimization,” “non-violent victimization,” and/or “victimization not otherwise specified.” The median prevalence rate for violent victimization was 20%, for sexual victimization 20%, nonviolent victimization 19%, and for victimization not otherwise specified 19%. Victimization rates were approximately 4–6 times higher than in the general community. Meta-analyses showed the following significant risk factors: delusion (OR = 1.69), hallucinations (OR = 1.70), manic symptoms (OR = 1.66), drugs (OR = 1.90) or alcohol abuse (OR = 2.05), perpetration of a crime (OR = 4.33), unemployment (OR = 1.31), and homelessness (OR = 2.49). Other risk factors like previous victimization, impaired social functioning, personality disorder, and living in a disadvantaged neighborhood were found only in 1 or 2 studies. Based on the results, we conclude that, depending on the examined time period, 1 in 5 (assessment period ≤3 y) or 1 in 3 (assessment period entire adulthood) people with a psychotic disorder was victim of a crime. Clinical, behavioral, and sociodemographic factors were significantly associated with victimization, as well as previous victimization. Prospective research into risk factors is needed to capture causal trajectories of victimization.